Guidelines for the diagnosis, prevention and management of chemical- and radiation-induced cystitis. (January 2014) - Thompson, A; Adamson, A; Bahl, A; Borwell, J; Dodds, D; Heath, C; Huddart, R; Mcmenemin, R; Patel, P; Peters, J; Payne, H
Objective: Haemorrhagic cystitis (HC) is a relatively common complication of chemotherapy and radiotherapy to the pelvic area, but can be a challenging condition to treat, particularly since there is currently a lack of UK-led guidelines available on how it should optimally be defined and managed. Materials and methods: A comprehensive literature search was undertaken to evaluate the evidence for the diagnosis, prevention and management of cancer treatment-induced HC. Results: Recommendations and a proposed management algorithm for the diagnosis, prevention and treatment of HC, as well as the management of intractable haematuria, have been developed based on the expert opinion of the multidisciplinary consensus panel following a comprehensive review of the available clinical data. Conclusion: These guidelines are relevant and applicable to current clinical practice and will help clinicians optimally define and manage this potentially serious condition.